IMPLEMENTASI KEBIJAKAN PEMBERIAN IZIN USAHA MIKRO DAN KECIL DI KANTOR KECAMATAN MALALAYANG KOTA MANADO - Tampan, Abner; Rumapea, Patar; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Implementation of policies granting of micro and small enterprises aims to give consent tomicro and small businesses for people who have small businesses and small that their enterprises have thelegality / validity of the government, but in fact the service performed has not gone up, therefore, this study isintended to answer questions about how the implementation of policies granting of micro and smallenterprises. In this study, researchers used a model of implementation of the George C. Edward III, wherethe implementation level visits from four aspects which have great impact in policy implementation.Communication is an aspect for the government to inform policy to the public as target group. Adequateresources both human resources and financial resources will affect the success rate policy. Disposition is theattitude held by implementing policies such as ethics and commitment to make this policy succeed. Thebureaucratic structure is the operational structure of the mechanisms of services and organizationalstructure of the implementing agency policies. In this research using descriptive qualitative research methodis through interviews with 10 informants, direct observation and document searches in connection with thepolicy, even in research assisted by the interview, a tape recorder and stationery menulis.Hasil research ingeneral explained that the Implementation Granting Policy for Micro And Small at the District OfficeMalalayang has not gone up.Keywords: Policy Implementation, License Micro And Small